Properties of Grassland Habitats in Organic and Conventional Farms Located in Mountainous Areas—A Case Study from the Western Sudetes - Krzysztof Solarz; Agnieszka Dradrach; Marta Czarniecka-Wiera; Adam Bogacz; Anna Karczewska (Agriculture)
Organic farming is becoming increasingly important in agricultural production, especially in mountain and foothill areas. In organic farms, unlike conventional ones, no mineral fertilization or chemical plant protection is used, which often limits the economic efficiency of production. It is commonly believed that conventional farming poses a threat to biodiversity due to the use of mineral fertilization, chemical plant protection, and highly productive crop varieties, and the products obtained are in many respects of lower quality than those from organic farms. The aim of this work is to compare the quality and fertility of soils and the biodiversity of grasslands in organic and conventional farms, using the example of a foothill area within the commune of Kamienna Góra located in the Western Sudetes. Thirty-three areas representing 11 farms that produce dairy cattle in a grazing system were selected for analysis. The properties of soils in organic and conventional farms and their nutrient status did not differ significantly, except for the content of available potassium, which was higher in the group of organic farms. This fact seems to be related to the type of parent rock. All soils had acidic, slightly acidic, or strongly acidic pH levels. The greatest differences between pastures in organic and conventional farms concerned the sward species composition and biodiversity indices. Grasslands in organic farms were much richer in species, which was reflected by the species richness (SR) index and the F-fidelity index. The species inventoried clearly formed two groups that are characteristic of organic and conventional grasslands. The greater biodiversity of grasslands in organic farms did not have a significant effect on the fodder value of the sward, which should be considered good, allowing producers to participate in short supply chains. However, in all farms, regardless of their type, it would be advisable to carry out gentle liming.